(untitled) (Revista da Faculdade de Odontologia - UPF, 2013)
Angina bullosa hemorrhagica is a disorder of unknown etiology characterized by the sudden onset of blood blisters in the oral and oropharyngeal mucosa. Objective: The present study describes six cases of patients diagnosed with ABH affecting the soft palate and tongue. Lesions appeared after meals, suggesting mastication trauma as the probable causative factor. From six, 04 occurred in the soft palate and 02 in the tongue, showing firstly a bubble blood, and subsequently to its rupture, the appearing of an ulcer. Final consideration: The authors discuss diagnostic criteria, essentially based on clinical data, as well as possible treatment approaches.